Renal histopathology in acute kidney injury following haemotoxic snake envenomation - P Sai Kameshwar Rao; Chanaveerappa Bammigatti; P S Priyamvada; Bheemanathi Hanuman Srinivas (Transactions of The Royal Society of Tropical Medicine and Hygiene, 2026)
Abstract Objectives Snakebite envenomation is a major cause of acute kidney injury (AKI) in tropical regions. While acute tubular necrosis (ATN) and acute cortical necrosis have traditionally been described as predominant renal lesions, multiple factors, including recent improvements in early access to antivenom, may have altered the histopathological spectrum. This study aimed to evaluate renal histopathology in snakebite envenomation-associated AKI (SBE-AKI) and its clinicopathological correlates. Methods In this prospective observational study conducted at a tertiary care centre in South India from September 2022 to July 2024, patients with proven haemotoxic snake envenomation who developed persistent AKI were included. Kidney biopsies were performed in survivors after correction of coagulopathy, and autopsy biopsies were obtained from non-survivors. Histopathological assessment was independently performed by two blinded pathologists. Results Eighteen renal biopsy samples were analysed. ATN and acute interstitial nephritis (AIN) were the most frequent lesions (each 38.9%), followed by thrombotic microangiopathy (16.7%) and pigment nephropathy (5.5%). Notably, no cases of cortical necrosis were identified. Early recognition and treatment of AIN with corticosteroids were associated with complete renal recovery in selected survivors. Conclusion The predominance of AIN and absence of cortical necrosis suggest an evolving histopathological pattern of SBE-AKI. Early renal biopsy may help identify potentially reversible lesions and improve renal outcomes.